Analisi Campur Kode Dalm Percakapanpada Unggahan Tiktok @Hellorays_: Kajian Sosiolinguistik - Ledy Novwanty Nainggolan; Tabita Simaremare; Mutiara Aprilia; Mannawa salwa; Delfira Almuharomah Lubis; Grace Evelyn Hutabarat; Ayu Nadira Wulandari (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to analyze the form, function, causal factors, and syntactic structure of code-mixing in conversations posted by the TikTok account @hellorays_. This study used a qualitative method with a descriptive sociolinguistic approach. Data in the form of utterances containing code-mixing were collected through documentation and note-taking techniques, then analyzed descriptively. The results indicate that the dominant code-mixing is intra- sentential code mixing, which involves the interpolation of English into Indonesian within a single sentence. Syntactically, code-mixing occurs at the word, phrase, and clause levels without disrupting the primary structure of Indonesian. The use of code-mixing serves as a means of expression, social identity formation, familiarity, and linguistic aesthetics. Contributing factors include digital globalization, lifestyle, communication efficiency, and emotional context. Thus, code-mixing on social media reflects linguistic creativity and communication strategies for constructing identity in the digital age.